Spatial Analysis of Criminality Based on Open Data of Czech Police (PČR) - Hatiarová, Dominika (2025)
This thesis aims to examine the effects of various socioeconomic factors on the prevalence of drug-related criminal offenses in the Czech Republic and to uncover the most problematic geographical areas. The methodology is based on the application of exploratory spatial data analysis techniques and statistical modeling, including the use of spatial econometric models and models for count data. The analysis reveals three clusters of administrative units exhibiting elevated crime rates, all located in the northern or north-eastern regions of Czechia. The results of the regression analysis based on the negative binomial model indicate that the divorce rate, and the proportion of young men and individuals with low education in the population significantly increase drug-related crime rates. The positive effect of the unemployment rate is not found to be statistically significant. A change in the share of foreigners and the number of living allowances per 1000 inhabitants is associated with a decrease in the crime rate; however, both of these effects are likewise shown to be insignificant.